Hope and Disappointment By Trisutji Kamal: Analysis Vocal and Piano Music Composition - Manalu, Kartini R. M.; Simanjuntak, Hendrik L; Waruwu, Happy Majesty; Simanjuntak, Octavia Indri (Jurnal Mamangan, 2023)
Trisutji Kamal is the first Indonesian female composer to work in the field of 'Indonesian classical music', and her works have become part of the repertoire of various musical performances, concerts, and recitals both domestically and internationally. His compositions are manifestations of personal experience, identity, nationalism, love and beauty, developed using various compositional techniques connected to various trajectories of Western music history. In this position, the author sees Trisutji Kamal as having entered a phase of providing novelty in composition, namely by discussing a 'new' compositional form. This 'new' compositional form has directly opened up a space for discussion regarding aesthetics, appropriateness, temporality, and also interpretation. The Cycle: Hope and Disappointment is a different cycle from those of Schubert and Schumann. Trisutji Kamal presents different times within the cycle and various themes, thus creating a distinct continuity. This certainly impacts the performance and the way the text is conveyed to the audience. According to the author, this is one of Trisutji Kamal's compositional strengths that has not been widely discussed in scholarly discussions and previous research. Through a qualitative approach, this research opens up space to see the relationship between Trisutji Kamal's work and Schubert and Schumann and to discuss different things as part of 'newness' in composition.